Tambaqui growth reared in cages in a floodplain lake under different feeding rate - Chagas, Edsandra Campos; Gomes, Levy de Carvalho; Júnior, Heitor Martins; Roubach, Rodrigo; Lourenço, José Nestor de Paula (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this work was to estimate the effect of feeding rates, 5%, 7.5% and 10% of body weight per day, on growth performance and metabolic parameters of tambaqui, Colossoma macropomum, reared in cages located in a floodplain lake. Fish fed at 5% of body weight per day presented better feed conversion; total plasma protein values, after 90 days, were significantly lower than in other treatments. A daily feeding rate of 5% body weight, for tambaqui juveniles reared in cages in floodplain lakes, allows a satisfactory performance.